Diskurse - Institutionen - Individuen Neue Perspektiven in der Übergangsforschung - Pohling, Andrea (Reflexive Übergangsforschung - Doing Transitions., 2022)
Life is structured by a great variety of transitions. How do transitions take place between individual phases of life and status positions, between different roles and self-images? How are transitions discursively negotiated? The contributions in this volume deal with how transitions are produced and shaped through discourse, institutional regulation, and individual learning and coping processes.